Inisiasi Tunas Ganda Tanaman Manggis Malinau melalui Kultur In Vitro untuk Perbanyakan Klonal - Lestari, Endang Gati; Suhartanto, M. Rahmad; Kurniawati, Ani; Rahayu, Suci (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
Mangosteen (Garcinia mangostana L.) is one of the most promising tropical fruits for export. The major constraint toincrease fruit production of the spesies is the long juvenile period. Seedless, sweet and juicy variety of mangosteen had beenfound in Malinau. In vitro propagation technique offers possibility to produce sufficient number of seedlings any time. Thisresearch was aimed at obtaining the appropriate media formula to enhance shoot proliferation. This research consisted ofshoot induction and multiplication and shoot elongation. The materials were the fresh mangosteen seeds from the Malinaumangosteen trees. The explant used in the trial was seeds which were divided into four slices. The use of 8 to 16 mg BA L-1combined with 0.2 mg thidiazuron L-1 resulted in the best shoot induction of 52 shoot buds per explant at the 6th week afterplanting with the mean height of 0.3 cm. Upon subculturing in to the similar media, the number of shoot tends to increase.For multiplication, low concentration of BA (2 to 4 mg L-1) and thidiazuron 0.05 mg L-1 were applied to increase the numbersof shoots. The total shoot number obtained in the media with 0.05 thidiazuron without BA was 11.25 and in the media with 2mg BA L-1 + 0.05 mg thidiazuron L-1 was 8.7 shoot explant-1. The result showed that the best media for shoot elongation wasMS + 1 mg BA L-1 + 2 mg kinetin L-1. The length of the shoots were in the range of 0.5-0.8 cm.Keywords: BA, Garcinia mangostana, in vitro culture, shoot multiplication, thidiazuron